Subcutaneous Peripheral Nerve Field Stimulation for the Treatment of Chronic Back Pain: Patient Selection and Technical Aspects - Winkelmueller, Matthias; Kolodziej, Malgorzata Anna; Welke, Wolfgang; Koulousakis, Athanasios; Martinez, Ramon (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
A wide variety of therapeutic options are available for the treatment of chronic back pain, a very common condition in Western countries with high related social and economic costs. Nevertheless, it is not always possible to achieve adequate long-term pain relief in spite of intensive analgesic therapies. Subcutaneous peripheral nerve field stimulation (sPNFS) is a newly approved neuromodulative treatment for back pain. In previously reported case series, it has provided encouraging results on long-term pain relief, improvement in quality of life, and a reduced need for analgesic drugs. Although the surgical technique is simple, there is neither consensus for patient management nor a standardized procedure for the implantation procedure. After consideration of our personal experience and the published literature, a basic recommendation has now been developed. This represents the first step toward planning prospective studies and standardization of this treatment and will permit comparison of this technique and the results with sPNFS.
Keywords: peripheral nerve; stimulation; chronic; back; pain